The Association Between Training Perceptions and Self-Reported Performance: A Case Study of Social Forestry Employees in Indonesia - Ananda Muchksin Maraja Riforio; Moh. Aris Pasigai; Ismail Rasulong (INCOME: Innovation of Economics and Management, 2025)
This study examines the association between training perceptions and employee performance in a social forestry administration in Indonesia. A quantitative, cross-sectional survey was conducted at the Balai Perhutanan Sosial dan Kemitraan Lingkungan Sulawesi, Section One, Bili-Bili, Gowa, involving all forty employees who had participated in formal training programs. Data were collected through a structured questionnaire and supported by brief interviews and document review. Results indicate generally favorable perceptions of training and high self-reported performance levels. Regression analysis shows a strong positive correlation between training and performance, suggesting that well-delivered and relevant training is associated with higher perceived effectiveness, timeliness, and initiative. However, as the data are cross-sectional and self-reported from a single organization, causality cannot be inferred. The findings are preliminary and should be interpreted as indicative rather than conclusive. They highlight potential areas for further investigation on how communicative instruction, relevant materials, and interactive methods contribute to improved workplace outcomes. Future research employing longitudinal and multi-source designs is needed to verify these relationships and support evidence-based policy development in public sector training.